Listado de especies espinosas de Solanum L. (Leptostemonum, Solanaceae) - Clara Inés Orozco; Gabriel D. Beltrán; Natalia Porras; Michael Nee (Biota Colombiana, 2008)
Solanum is one of the largest flowering-angiosperm genera with 1500 species approximately. Five clados are recognized in Solanum, Leptostemonum is the largest group with 350-450 species distributed in the Old and Neotropic world. In the Neotropic 200 species are recognized. This study is an initial base for posterior studies of taxonomic and evolution diversity of Leptostemonum. The checklist of the names presented here is the result of the study of herbaria COL, COAH, FMB, HUA, JAUM, UPTC, INPA and MG collections and the revision of data bases as International Plant Name Index, Solanaceae Source, The New York virtual Herbarium and Tropicos. There were found 54 valid and effective-published names, 12 of these names associated to 14 synonyms in Colombia.